2015
DOI: 10.1021/np501030r
|View full text |Cite
|
Sign up to set email alerts
|

Striatoids A–F, Cyathane Diterpenoids with Neurotrophic Activity from Cultures of the FungusCyathus striatus

Abstract: Six new highly oxygenated polycyclic cyathane-xylosides, named striatoids A-F (1-6), were isolated from the cultures of the basidiomycete Cyathus striatus. Their structures were established by comprehensive spectroscopic analysis including 2D NMR (HMBC, HSQC, ROESY, (1)H-(1)H-COSY) and HRESIMS experiments. Compounds 2 and 3 possess an unusual 15,4'-ether ring system. The isolated compounds dose-dependently enhanced nerve growth factor (NGF)-mediated neurite outgrowth in rat pheochromocytoma (PC-12) cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 30 publications
(19 reference statements)
1
58
0
Order By: Relevance
“…Known as birdʼs nest fungi, several Cyathus species produce novel compounds with biological activities such as antibiotic, antifungal, anti-neurodegenerative, antioxidative, and anti-inflammatory activities [38], and some cyathanes are specific to this genus. Gao et al isolated several cyathane diterpenoids with a contiguous 5/6/7 tricyclic skeleton from Cyathus species with neurotrophic activity [39][40][41]. Six highly oxygenated polycyclic cyathanexylosides, designated striatoids A-F (16)(17)(18)(19)(20)(21), were shown to be isolated from the liquid cultures of Cyathus striatus (Huds.)…”
Section: Cyathus Sppmentioning
confidence: 99%
See 1 more Smart Citation
“…Known as birdʼs nest fungi, several Cyathus species produce novel compounds with biological activities such as antibiotic, antifungal, anti-neurodegenerative, antioxidative, and anti-inflammatory activities [38], and some cyathanes are specific to this genus. Gao et al isolated several cyathane diterpenoids with a contiguous 5/6/7 tricyclic skeleton from Cyathus species with neurotrophic activity [39][40][41]. Six highly oxygenated polycyclic cyathanexylosides, designated striatoids A-F (16)(17)(18)(19)(20)(21), were shown to be isolated from the liquid cultures of Cyathus striatus (Huds.)…”
Section: Cyathus Sppmentioning
confidence: 99%
“…Willd. for the first time [39]. Among the isolated striatoids, striatoids B (17) and C (18) borne a rare 15,4′-ether ring system with significant neurotrophic activity in PC12 cells [39].…”
Section: Cyathus Sppmentioning
confidence: 99%
“…Morphologic analysis and quantification of neurite-bearing cells were performed using a phase-contrast microscope as described previously [18,27]. PC-12 cells were seeded on poly-L-lysine-coated 24-well plates at a density of 2 × 10 4 cells/mL in DMEM + 10% HS, 5% FBS, 100 IU/mL penicillin, and 100 μg/mL streptomycin at 37 °C under a humidified atmosphere of 95% air and 5% CO 2 for 24 h. Cells without treatment served as a negative control.…”
Section: Plant Material:mentioning
confidence: 99%
“…Cell viability assays showed that the test compounds had no toxic effects on PC-12 cells at concentrations up to 25 µM (data not shown). To study whether these compounds exhibit neurotrophic properties in PC-12 cells, neurite outgrowth in the culture media was measured according to our previously reported experimental procedure [27]. Then the cells were incubated with the compounds 1−9 at concentrations of 25 μM in the absence or presence of NGF (20 ng/mL).…”
mentioning
confidence: 99%
“…203 A number of new cyathane diterpenoids have been isolated including the striatoids A-F (e.g. A, 59) from the basidiomycetes, Cyathus striatus, 204 and from C. africanus 205 and Hericium erinaceus. 206 The total synthesis of the guanacastepenes N and O, 207 dolestatrienol, 208 and the trichoaurantiolides C and D 209 have been reported.…”
Section: Miscellaneous Diterpenoidsmentioning
confidence: 99%